Millets: A Promising Pathway in Combating Food Crisis - Jaidka, Manpreet; Kaur, Ramanjit; Singh, Teekam; Meena, S. L. (Chronicle of Bioresource Management, 2023)
Millets are coarse grains whose cultivation on fertile as well as marginal lands dates back to 3500-2000 BC. Millets are classified as large millets and small millets on the basis of size of the grain. Millets, with low glycemic index act as a store house of nutrients prove propitious in combating various heath related issues. These are recognized as climate smart crops due to their adaptation to diverse agro-climatic conditions and presence of diverse pool of genes to perform under abiotic stress. Millets can also be called as “Miracle Grains” as they require less water, less dependence on synthetic fertilizers, provide sustainable food and fodder and fit well in contingent crop planning. Government of India celebrated the year 2018 as “National Year of Millets” to create greater awareness by addressing millets as nutricereals. Other ventures of GOI, like increase in MSP for millets, formation and promotion of self-help groups by civil societies etc. paved a way for successful adoption for cultivation of millets. The tribal community in the Bastar Plateau Zone of Chhattisgarh in India clearly demonstrates the ethno-medical uses of millets and by-products. In the times of sedentary lifestyle, less diversity in source of nutrition and demand for nutritious diet, an increase in awareness and knowledge regarding the millets by proper planning and execution of awareness campaigns, public education has become need of the hour.